CBCT measurement of labial bone thickness of mandibular anterior teeth and depth of medial lingual foramina and their clinical significance - ZENG Shijin; LI Shuhong; ZHOU Liping; XIE Cuiliu (Kouqiang hemian waike zazhi)
[Objective:] To measure the labial bone thickness of mandibular anterior teeth and depth of medial lingual foramina (MLF) by cone beam CT (CBCT) and to provide data for immediate implant in the mandible anterior region. [Methods:] Two hundred patients aged 18 to 40 years old were selected. CBCT was used to measure the labial bone thickness at 2.0 mm (P1), 5.0 mm (P2) and 8.0 mm (P3) below the enamel-cemental junction of mandibular central incisors, mandibular lateral incisors and mandibular canines, and the distance between the MLF and the alveolar crest. The means and standard deviations were calculated, and the data was statistically analyzed by SPSS 25.0. [Results:] At P1, the percentage of the thickness of mandibular central incisors, lateral incisors and canines less than 1.0 mm was 81.0%, 87.0% and 91.5%; at P2, the percentage of the thickness of mandibular central incisors, lateral incisors and canines less than 1.0 mm was 94.0%, 98.0% and 95.0%; at P3, the percentage of the thickness of mandibular central incisors, lateral incisors and canines less than 1.0 mm was 35.5%, 65.5% and 70.0% respectively. The labial bone thickness in male patients of mandibular central incisors at P2 and canines at P2 and P3 were thicker than that in female patients (P<0.05). The detection rate of MLF was 97.9% for male patients and 96.2% for female patients, with no significant difference (P>0.05). The closest distance between the MLF and alveolar crest was 11.4 mm. 7.2% of the distance were less than 14.0 mm, 78.4% of the distance were concentrated between14.0 mm and 24.0 mm, and 14.4% of the distance were more than 24.0 mm. The majority of MLF was 1, accounting for 72.2%, and the maximum number was 3. "Large lingual foramina" with excessive diameter was also found. [Conclusion:] Most of the labial bone thickness in mandible was less than 1.0 mm, and only got thickened at 8.0 mm below the enamel-cemental junction of mandibular central incisor. The MLF is generally safe for implant, but there are variations in location, number, and diameter.